Author Correction: Large intrinsic anomalous Hall effect in half-metallic ferromagnet Co3Sn2S2 with magnetic Weyl fermions. Issue 1 (December 2018) - Wang, Qi; Xu, Yuanfeng; Lou, Rui; Liu, Zhonghao; Li, Man; Huang, Yaobo; Shen, Dawei; Weng, Hongming; Wang, Shancai; Lei, Hechang
The original version of this Article incorrectly omitted an affiliation of Hongming Weng: "Beijing National Laboratory for Condensed Matter Physics and Institute of Physics, Chinese Academy of Sciences, 100190, Beijing, China" This has been corrected in both the PDF and HTML versions of the Article.